Design and implementation of a nonlinear controller for a robotic arm with flexible joints and rigid links - Padilla-Mora, Juan José (2017)
Proyecto de Graduación (Licenciatura en Ingeniería Mecatrónica) Instituto Tecnológico de Costa Rica, Área Académica de Ingeniería Mecatrónica, 2017.